2021
DOI: 10.1002/chem.202101505
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Coordination of Chloride and Fluoride Anions Towards Trivalent Lanthanide Cations (La3+ and Nd3+) in Molten Salts

Abstract: Molten salt electrolysis is a vital technique to produce high‐purity lanthanide metals and alloys. However, the coordination environments of lanthanides in molten salts, which heavily affect the related redox potential and electrochemical properties, have not been well elucidated. Here, the competitive coordination of chloride and fluoride anions towards lanthanide cations (La3+ and Nd3+) is explored in molten LiCl‐KCl‐LiF‐LnCl3 salts using electrochemical, spectroscopic, and computational approaches. Electroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…To probe the influence of halide anions X − , our group examined the complexation behaviors of La(III) and Nd(III) in LiCl−KCl−LiF melts [52] . It was revealed that after the introduction of LiF to molten LiCl−KCl−LnCl 3 , a competition between F − and Cl − ions for coordinating Ln(III) was observed.…”
Section: Coordination Chemistry Of Lanthanide Elements In Molten Saltsmentioning
confidence: 99%
See 2 more Smart Citations
“…To probe the influence of halide anions X − , our group examined the complexation behaviors of La(III) and Nd(III) in LiCl−KCl−LiF melts [52] . It was revealed that after the introduction of LiF to molten LiCl−KCl−LnCl 3 , a competition between F − and Cl − ions for coordinating Ln(III) was observed.…”
Section: Coordination Chemistry Of Lanthanide Elements In Molten Saltsmentioning
confidence: 99%
“…Ln 3+ ions are colored in orange, Cl − in green, F − in purple, Li + in blue and K + in red. Reproduced with permission [52] . Copyright 2021, Wiley‐VCH GmbH.…”
Section: Coordination Chemistry Of Lanthanide Elements In Molten Saltsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the 235 U fission byproducts in nuclear reactors is 152 Eu, which has a rich redox chemistry. Understanding the redox behavior and speciation of 152 Eu in a molten salt is an open challenge for developing molten salt separating strategies and high-temperature pyroprocessing techniques. , Previous studies have been dedicated to understanding the redox reaction of Eu­(II)/Eu­(III) and the local structure and transport properties of Eu ions, as well as other lanthanides, in the LiCl–KCl eutectic molten salt. The redox mechanism of Eu­(II)/Eu­(III) has been investigated with electrochemical methods, in which the diffusion coefficients of Eu 2+ and Eu 3+ can be measured. ,, Recently, we investigated the influence of the outer-sphere cations M n+ (M = K, Na, n = 1; M = Ca, n = 2) on the redox potential of Eu­(III)/Eu­(II) by dissolving Eu 3+ in their molten chloride salt MCl n . That work revealed that the reduction potential of Eu­(III)/Eu­(II) shifted positively and facilitated the formation of Eu 2+ when outer-spere cations, that were strongly polarizing, were present in the molten salt.…”
Section: Introductionmentioning
confidence: 99%
“…Salt melts based on LiF-BeF 2 and LiF-NaF-KF have been verified as promising media ensuring the operation of liquid-salt reactors with low overpressure. 1,2 Molten alkaline and alkaline Earth metal fluorides [3][4][5][6] and chlorides 7,8 demonstrate excellent hydrodynamic and heat exchange properties, low vapor pressures in a wide operating temperature range (from 500 °C to 850 °C) and do not interact with fuel in case of leakage. However, molten fluorides are aggressive to metallic structural materials.…”
mentioning
confidence: 99%